PERKEMBANGAN DAN HAMBATAN MAKAN LARVA Crocidolomia pavonana YANG DIBERI SEDIAAN FRAKSI DIKLORMETAN KULIT BATANG Calophyllum soulattri - Syahputra, Edy; Prijono, Djoko (Jurnal Agroteknos, 2011)
ABSTRACKThe objectives of this study were to evaluate the develovment time, and feeding inhibity of Crocidolomia pavonana larvae fed dichloromethana fraction of Calophyllum soulattri bark preparation.   Fractionation of C. soulattri fraction was performed with vaccuum liquid chromatography.   Bioassay was conducted against C. pavonana larvae by leaf-feeding method.  Second-instar C.  pavonana larvae  were  fed  extract-treated broccoli leaves for 48 haurs, then were presented with untreated leaves until the surviving larvae reached the fourth-instar stage.   The number of dead larvae was recorded.   For  feeding inhibity, preparation was assayed using leaf-disc choice and no-choice test towards third- instar C. pavonana larvae. The results showed that dichloromethan fraction of C. soulattri barks possessed strong insecticidal activity against C. pavonana larvae with LC50  of 0,06%. The dichloromethan fraction at 0,06%-0,09% could prolong development time of instar II-III larvae  by  1,7-2,7  days.  In  choice  and  no-choice  leaf  disc  methods,  the  dichloromethan fraction at 0,02%-0,075% inhibited feeding of instar III larvae by 54,8%-100%.  Concerning with their potentiality, further studies are needed to identify insecticidal compounds in those active extracts.Keywords: Calophyllum soulattri, Crocidolomia pavonana, feeding inhibity, insecticidal activity